The Function of Dampeang in Luambek Performances in Sintuk Toboh Gadang - Oktavina, Lucia; Armez Hidayat, Hengki; Fauzan Yusman, Ahmad (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2025)
This study aims to reveal and describe the function of Dampeang in the Luambek performance in Sintuk Toboh Gadang. This study is qualitative research, using descriptive methods and conducting an analytical approach to Dampeang in the Luambek performance and the relationship between the two. The main instrument of the study is the researcher himself, assisted by stationery and a mobile phone. Data collection techniques are carried out through literature studies, direct observation, interviews, and documentation. The analysis of research data carried out is reducing data, presenting data, and verifying conclusions. The results of this study include; 1) the origin of Dampeang; 2) the description of the Dampeang text; and 3) the form of presentation of Dampeang in the Luambek performance. Then an analysis of the function of Dampeang in the Luambek performance was carried out until it was found; a) the function of emotional expression; b) the function of entertainment; c) the function of communication; d) the function of physical response; e) the function in carrying out the conformity of social norms, f) the function of ratifying social and religious institutions; and g) the function of contributing to the preservation and stability of culture. And, h) The function of Dampeang in Luambek performances from an educational value perspective.